Systems, uncertainty, and information: A legacy of George J. Klir. Issue 8 (17th November 2017) - Belohlavek, Radim
Abstract: This paper tracks scientific work and contributions of George J. Klir (1932–2016), one of the major figures in systems movement and the founder of this journal.